COMMITMENT OF KRI PATTIMURA CLASS CREW REVIEWED FROM SOLDIER MOTIVATION AND COMPENSATION - Verdianto, Joan; Arsanta, I Made Wira Hadi; Sadimin, Sadimin (JURNAL EKBIS, 2023)
In order to support the main tasks of the Navy and other tasks based on the policy of the Chief of Staff of the Navy, it is hoped that the crew of the ship (ABK) will always have good combat readiness. However, the current condition of the crew's combat readiness is still not optimal, which is indicated by several factors/variables including motivation and compensation. The purpose of this study was to analyze the effect of motivation and compensation simultaneously and partially on the level of combat readiness of ABK KRI Pattimura Class. This study uses quantitative methods with multiple linear regression techniques. The sample used was 83 ABK KRI Pattimura Class selected using the slovin formula from a total population of 264 personnel. The results showed that motivation and compensation simultaneously had a significant positive effect on the level of combat readiness of KRI Pattimura Class crew members. Motivation partially has a significant positive effect on the level of combat readiness of ABK KRI Pattimura Class and compensation partially has a significant positive effect on the level of combat readiness of ABK KRI Pattimura Class.